Weight monitoring as an indicator of re-hospitalization in patients with heart failure - Saha, Swapan; Kapoor, Manish; Ete, Tony; Nath, Dhanjit; Megeji, Rinchin Dorjee; Jha, Pravin Kumar; Kavi, Gaurav; Das, Chandra Kumar; Mishra, Animesh (International Journal of Research in Medical Sciences, 2016)
Background: Predicting the development of acute decompensated heart failure (ADHF) in chronic heart failure patients remains a challenge. Standard management of HF involves patient weight monitoring as it is generally accepted that body weight increase, reflecting fluid retention, may be of value in heralding imminent decompensation. Aim of the study was to evaluate body weight increment as an indicator of re-hospitalization in patients with heart failure. Methods: Fifty seven patients with principal diagnosis of heart failure, who got re-hospitalised due to decompensation as evidenced by deterioration of symptoms with increase in body weight, were analysed and compared with the parameters at last discharge with an attempt to look for the association between increase in weight and clinical deterioration. Results: Mean age of patients examined was 58.5 years. 54.4% of the patients were male. Mean weight of patients on re-hospitalization was 52.2 kg as compared to 48.8 kg at last discharge (p<0.05). 57.9% and 42.1% of patients presented in NYHA class IV & III respectively on re-hospitalization whereas all patients were discharged previously in NYHA class II status. Pearson chi-square test of association showed a significant deterioration of functional status (NYHA) in those having increase in weight ≥3kg as compared to <3 kg (p<0.05). Conclusions: A simple weight monitoring of heart failure patients can alert patients and their clinicians in early stages of decompensation preventing re-hospitalization.